The management Model of National Character Education for Early Childhood Education through based on Democracy - Hasnidar Hasnidar; Elihami Elihami (Edumaspul: Jurnal Pendidikan, 2019)
This study is aware of the management of Early Childhood Education through National Character Education based on Democracy. The problems of this study are: 1) What is the process of applying the management of Early Childhood Education through the National Character Education based on Democracy; 2) Can through the management of Early Childhood Education be implemented the National Character Education based on Democracy. The type of research used the classroom action research which seeks to examine and reflect in depth some aspects of teaching and learning activities. The focus of this research is the management of Early Childhood Education through National Character Education based on human resources and local education activities with the management of Early Childhood Education. The subjects was the subject of the study TK PGRI Standard Corawali, Sidenreng Rappang Regency, consisting of 25 children consisting of 10 boys and 15 girls. The instrument that will be used is observation, tests and documentation. Data to be processed by percentage analysis and presented in the form of descriptions and presentations. The implementation plan begins with asking questions, thinking together and answering; 2) Application of the approach to improving learning outcomes and increasing character in TK PGRI Standard Corawali to apply the character of children. The goals and objectives of education held in schools are formal and informal channels. The main target of education can be achieved well, it needs to be initiated in the concept of integration through a character approach to TK PGRI Standard Corawali.